PENGARUH PENAMBAHAN SILICA FUME DAN GLENIUM SKY TERHADAP KUAT TEKAN BETON K-400 - Kimi, Sudirman; Alghafari, Abdullah Abuzar (Universitas Muhammadiyah Palembang, 2019)
In the development of concrete technology (Concrete Technology) today which is increasingly unceasingly, along with the development of the era hence the quality of concrete selection as the main raw material of building construction is very important. This research writer take silica fume and glenium sky as added concrete mixture to know the influence of the addition of silica fume and glenium sky to the compressive strength of concrete. The research is divided into three stages : material testing, test object making and test object. This research uses cube-shaped specimen with size 15x15x15 cm, with 5 variations, they are normal concrete, silica fume 5%, silica fume 5% + glenium sky 2%, silica fume 5% + glenium sky 4%, and silica fume 5% + glenium sky 6%, which every variations has 3 test specimens with 3 days, 7 days, and 28 days. From laboratorium testing, the characteristics of compressive strength of concrete at age 28 days of normal concrete is 407,2 Kg/Cm2, normal concrete with silica fume 5% is 418,5 Kg/Cm2, normal concrete with silica fume 5% + glenium sky 2% is 435,9 Kg/Cm2, normal concrete with silica fume 5% + glenium sky 4% is 451,9 Kg/Cm2, normal concrete with silica fume 5% + glenium sky 6% is 484,1 Kg/Cm2.